The cost-effectiveness of transcatheter aortic valve implantation versus surgical aortic valve replacement in patients with severe aortic stenosis at high operative risk. Issue 13 (21st May 2013) - Fairbairn, Timothy A; Meads, David M; Hulme, Claire; Mather, Adam N; Plein, Sven; Blackman, Daniel J; Greenwood, John P
Abstract : Objective: To determine the cost-effectiveness of transcatheter aortic valve implantation (TAVI) compared with surgical aortic valve replacement (SAVR) in a high-risk aortic stenosis (AS) population. Design: A cost-utility analysis employing the National Institute of Clinical Excellence (NICE) reference case design for technology appraisals. Setting: The perspective of the UK National Health Service. Patients: Utility data from a UK high-risk AS population. TAVI and SAVR effectiveness was taken from the PARTNER A randomised controlled trial. Main outcome measures: Costs modelled over a 10 year horizon using a Markov model. Incremental cost-effectiveness ratios and cost-effectiveness acceptability curve were calculated with reference to the NICE willingness to pay per quality adjusted life year (QALY) gain threshold. Deterministic and probabilistic sensitivity analyses performed. Results: Despite greater procedural costs (£16 500 vs £9, 256), TAVI was cost-effective compared with SAVR over the 10 year model horizon (costs £52 593 vs £53 943 and QALYs 2.81 vs 2.75), indicating that TAVI dominated SAVR. This appeared to be due to greater postsurgical costs, related to the length and cost of hospital stay. The results appeared robust to a number of deterministic sensitivity and probabilistic analyses. The cost-effectiveness acceptability curve indicated that at the NICE £20 000 willingness to pay threshold per QALY gained, TAVI had a 64.6% likelihood of being cost-effective, compared with 35.4% for SAVR. Conclusions: TAVI is likely to be a cost-effective treatment for high-risk patients with AS compared with the reference standard of SAVR. However, uncertainty surrounding the long-term outcomes for TAVI patients remains; this could have a substantive impact on estimates of cost-effectiveness.